5.1k views
1 vote
I need help with these five questions

I need help with these five questions-example-1
I need help with these five questions-example-1
I need help with these five questions-example-2
I need help with these five questions-example-3
I need help with these five questions-example-4
I need help with these five questions-example-5

1 Answer

6 votes

Answer:

The fourth

The second

The first

The third

The fourth

Explanation:

h(x)+g(x)=x²+4x–3

p(x)=R(x)–C(x)=50x–(8x+250)=42x+250

g(x).h(x)=(4x+1)(x²–3)=4x³–12x+x²–3=4x³+x²–12x–3

(f/g)(x)=(6x–3)/(12x²–6x)=(6x–3)/(2x(6x–3))

=1/2x x≠0 (as the equation then will be undefined)

g(x)–f(x)=(x²+1)–(2x+5)=x²–2x–4

User Kmort
by
6.5k points